P-V-M Interaction Curves for Seismic Design of Steel Column Base Connections - Arlekar, Jaswant N.; Murty, C.V.R. (Engineering Journal, 2002)
Recent studies on connections have shown that the beam bending theory cannot predict the flow of forces near the connection regions. In this paper, a new truss analogy model has been proposed to better represent the flow of forces near the column base connections. Also, shear moment strength envelopes, generated for different levels of axial load using the hysteretic stress-strain curves for steel, are presented. The moment and shear demand for the design of column base connection elements are calculated using the normalized P-V-M interaction curves. Appropriate strength factors applied to the moment capacity of the column section to account for the uncertainty in the estimation of yield stress, strain hardening, compactness of the section, and slenderness of the member are discussed. Finally, a generalized procedure for the capacity design of column base connections is proposed.